2009
DOI: 10.3846/1648-6897.2009.17.164-170
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ultraviolet (Uv) Radiation From Technical Sources/Dirbtinių Šaltinių Skleidžiamos Uva Ir Uvb Spinduliuotės Įvertinimas/Определение Уфа- И Уфб-Излучений От Техногенных Источников

Abstract: Abstract. The paper presents the assessment of ultraviolet radiation from technical sources. It has been determined that the intensity of UVA radiation is about 10 times higher than the intensity of radiation of UVB. It has been investigated that the intensity of UV radiation during the welding process nonlinearly depends on the strength of the current, namely, if the strength of the current is reduced by 60%, the intensity of UV radiation is reduced by 20%, it also depends on the distance from the source, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…The International Commission on Non-Ionizing Radiation Protection (ICNIRP) declares which part of UVC spectrum with wave lengths below 180 nm (vacuum UV) are readily absorbed in air (17). That was consistent with study by Klein et al in which the results revealed using more sensitive spectroradiometer and UV irradiance was discernible at 300 nm, and in less values, wave length of the UV irradiance was not detected, while all of bulbs emit UV in the UVA and UVB range (16) (20). The highest UVA irradiance was recorded in 90°, for UVA radiation, occupational exposure limited should be limited to 1.04166 W.m -2 , of all of the bulbs tested, the Etehad appear to be the safest.…”
Section: Discussionsupporting
confidence: 81%
“…The International Commission on Non-Ionizing Radiation Protection (ICNIRP) declares which part of UVC spectrum with wave lengths below 180 nm (vacuum UV) are readily absorbed in air (17). That was consistent with study by Klein et al in which the results revealed using more sensitive spectroradiometer and UV irradiance was discernible at 300 nm, and in less values, wave length of the UV irradiance was not detected, while all of bulbs emit UV in the UVA and UVB range (16) (20). The highest UVA irradiance was recorded in 90°, for UVA radiation, occupational exposure limited should be limited to 1.04166 W.m -2 , of all of the bulbs tested, the Etehad appear to be the safest.…”
Section: Discussionsupporting
confidence: 81%
“…LSR increases from water (blue dots) to vegetated areas (green cluster), to arid zones (yellow cluster) with the highest resultant returns from snow/ice-affected zones (purple cluster). This finding agrees with some previous works, such as Chadysiene and Girgzdys 9 who had demonstrated that snow and sand surfaces reflect ~ 80% and ~ 25% of UV radiation, respectively, while grass yields the weakest reflectance. More interestingly, the difference between the strongest signal (snow) and weakest signal (water) in LSR, we revealed, is similar to the difference between dark and white surfaces, reported by the early work of Reagan and Zielinski 8 .…”
Section: Resultssupporting
confidence: 93%
“…In practice, the earlier work of Reagan and Zelinski 8 suggested that the lidar sensitivity of white surfaces (e.g., snow) is ~ 20 times greater than that of dark soil at visible wavelengths. Some further studies predicted that the backscatter lidar signals from white surfaces would be especially high at 355 nm 9 . Weiler 4 more recently used 355 nm data from the Aeolus pre-launch dedicated Airborne Demonstrator consisting of a High-Spectral resolution wind UV lidar that had been specifically developed to follow a similar measurement principle and specification 10 of the spaceborne instrument ALADIN planned for the Aeolus mission.…”
Section: Introductionmentioning
confidence: 99%
“…In Table 2, the mean values between 150 and 180s of irradiation time are presented. The fluence rate strongly decreased with increasing DTL and is conversely proportional to the square of the distance from the source (Jin et al, 2005) or coincide with the power trend line (fluence rate x DTL) (Chadyšiene et al, 2009). These findings were validated and resulted in R² ranging from 0.995 (0 HDPE) to 1.000 ( 4 1.67 ± 0.01 19.4% 3.2.…”
Section: Uvc Transmission Of Hdpe-foilmentioning
confidence: 62%